Increased arterial stiffness and reduced cardiovagal baroreflex sensitivity with anti cancer chemotherapy. - Frye, Jacob Nathaniel (Kansas State University, 2017)
Background – Chemotherapy-induced left ventricular cardiotoxicity is associated with many cancer treatments; however, what is less known is how these treatments affect vascular health and autonomic control of blood pressure. Arterial stiffness and cardiovagal baroreflex sensitivity (BRS) are indicators of cardiovascular health and may provide insight into the adverse effects of anti-cancer chemotherapy. Therefore, the primary aims of the present study were to evaluate carotid artery stiffness and arterial BRS in cancer patients currently being treated with adjuvant chemotherapy. Methods – We performed a cross-sectional, case-control study involving 9 cancer patients and 9 age- and sex-matched controls. Carotid artery stiffness was assess via 2D ultrasonography. Cardiovagal BRS was assessed from the spontaneous changes in beat-to-beat time series of R-R interval and systolic blood pressure via the cross correlation technique. Results – Our findings indicated a significant decrease in cardiovagal BRS in cancer patients compared to controls (4.7 ± 0.6 vs 9.2 ± 1.7 msec mmHg⁻¹ respectively, P = 0.02). Carotid artery β-Stiffness was significantly higher in the cancer patients compared to control participants (9.2 ± 1.2 vs 6.6 ± 0.74 U respectively, P = 0.05). Conclusions – These data suggest that anti-cancer chemotherapy elicits significant decreases in the autonomic control of blood pressure and arterial stiffness, leaving cancer survivors with an increased risk of future cardiovascular disease.
Keywords: Cancer; Chemotherapy; Baroreflex; Arterial stiffness